Modeling drying cracks in soils using a mesh fragmentation method - Sánchez, M.; Manzoli, O. [UNESP]; Guimarães, L. (Taylor & Francis, 2015)
Desiccation cracks in soils act as a preferential path for water flow and pollutant transport. Drying cracks also affect soil strength and may lead to stability in embankments and slopes. The presence of desiccation cracks can also trigger landslides.Vital infra-structure affected by soil cracking includes levees, road embankments and engineered barriers. Drying cracks generally develop in the soil mass forming a network of cracks with quite regular characteristics.The phenomena of crack generation in soils and sub-sequent propagation is quite complex. A number of factors control the start of the drying crack including soil properties, boundary conditions and soil heterogeneities. Good agreements between experimental results and model prediction are observed. © 2015 Taylor & Francis Group, London.